2017
DOI: 10.4103/0253-7176.211743
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Pattern and Sleep Hygiene Practices among Nigerian Schooling Adolescents

Abstract: Background:Sleep problems, especially in the adolescent stage of development, may be associated with excessive daytime sleepiness, impaired neurocognitive function, and a host of others leading to suboptimal performance.Objectives:To determine the pattern of sleep problems in school-going adolescents based on the bedtime problems; excessive daytime sleepiness; awakenings during the night and problems falling back asleep; regularity and duration of sleep; sleep-disordered breathing (BEARS) sleep screening algor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
6

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 18 publications
0
6
6
Order By: Relevance
“…Our ndings revealed that 12.2% of the participants rated themselves to have PSQ. Evidence from previous studies among adolescents, such as in the USA [5], Taiwan [7], Turkey, [29] and Nigeria [3,4] revealed higher rates, compared to the current report, which is higher than what was reported in India [30]. The disparity in rates may be related to the differences in research tools used to assess sleep quality, the de nition of terms, as well as the age of the participants.…”
Section: Discussioncontrasting
confidence: 79%
See 4 more Smart Citations
“…Our ndings revealed that 12.2% of the participants rated themselves to have PSQ. Evidence from previous studies among adolescents, such as in the USA [5], Taiwan [7], Turkey, [29] and Nigeria [3,4] revealed higher rates, compared to the current report, which is higher than what was reported in India [30]. The disparity in rates may be related to the differences in research tools used to assess sleep quality, the de nition of terms, as well as the age of the participants.…”
Section: Discussioncontrasting
confidence: 79%
“…An earlier study has reported a different rate of sleep-related problems at different stages of adolescent development, with a lower rate at the early adolescence compared to late adolescence [4]. While the ranked mean age of those who reported poor quality of sleep in the present study was higher than those who did not, the difference was not statistically signi cant.…”
Section: Discussioncontrasting
confidence: 76%
See 3 more Smart Citations